Delegated Coordination - Lara, Lucas Panico de (2019)
We consider a multi-dimensional model of delegation in which a principal makes a decision so as to coordinate two agents, each with private information of their own impacting the outcomes of the decision and with one agent having finer and the other having coarser information. We solve the model for a class of such cases and show that the principal is able to use each agent's uncertainty about the other's information as a screening device, leading to an optimal mechanism that is both more complex and more favorable to the principal than the simpler mechanisms in standard one-dimensional models of delegation. We also show that these results have consequences for the optimal flow and distribution of information inside organizations.